Association of mitochondrial DNA levels with frailty and all-cause mortality. - Ashar, Foram N; Moes, Anna; Moore, Ann Z; Grove, Megan L; Chaves, Paulo H M; Coresh, Josef; Newman, Anne B; Matteini, Amy M; Bandeen-Roche, Karen; Boerwinkle, Eric; Walston, Jeremy D; Arking, Dan E (J Mol Med (Berl), 2015)
Mitochondrial function is altered with age and variants in mitochondrial DNA (mtDNA) modulate risk for several age-related disease states. However, the association of mtDNA copy number, a readily available marker which reflects mitochondrial depletion, energy reserves, and oxidative stress, on aging and mortality in the general population has not been addressed. To assess the association between mtDNA copy number and two primary outcomes--prevalent frailty and all-cause mortality--we utilize data from participants who were from two multicenter, multiethnic, community-based, prospective studies--the Cardiovascular Health Study (CHS) (1989-2006) and the Atherosclerosis Risk in Communities (ARIC) study (1987-2013). A total of 4892 participants (43.3% men) from CHS and 11,509 participants (44.9% men) from ARIC self-identifying as white or black were included in the analysis. mtDNA copy number, the trait of interest, was measured using a qPCR-based method in CHS and an array-based method in ARIC from DNA isolated from whole blood in participants from both cohorts. In race-stratified meta-analyses, we observe a significant inverse association of mtDNA copy number with age and higher mtDNA copy number in women relative to men. Lower mtDNA copy number was also significantly associated with prevalent frailty in white participants from CHS (OR 0.91, 95% CI 0.85-0.97). Additionally, mtDNA copy number was a strong independent predictor of all-cause mortality in an age- and sex-adjusted, race-stratified analysis of 16,401 participants from both cohorts with a pooled hazard ratio of 1.47 (95% CI 1.33-1.62) for the lowest quintile of mtDNA copy number relative to the highest quintile. Key messages: Mitochondrial DNA (mtDNA) copy number is associated with age and sex. Lower mtDNA copy number is also associated with prevalent frailty. mtDNA copy number is a significant predictor of all-cause mortality in a multiethnic population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; DNA, Mitochondrial; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Dosage; Geriatric Assessment; Humans; Kaplan-Meier Estimate; Male; Mortality; Odds Ratio; Population Surveillance; Prospective Studies; Surveys and Questionnaires; United States